Puritans in the New World : a critical anthology - Hall, David D. (Princeton University Press, 2004)
[This] is a collection of texts that illuminates the experience of being a Puritan in the New World. The book will be welcomed by all those who are interested in early American literature, religion, and history.-Back cover.